Associations between eating behaviours and cardiometabolic risk among adolescents in the Health Outcomes and Measures of the Environment study. Issue 2 (12th September 2022) - Zhang, Zhuoya; Li, Nan; Buckley, Jessie P.; Cecil, Kim M.; Chen, Aimin; Eaton, Charles B.; Kalkwarf, Heidi J.; Lanphear, Bruce P.; Yolton, Kimberly; Braun, Joseph M.
Summary: Background: Eating behaviours are associated with childhood obesity, but their associations with cardiometabolic risk are less clear. Objectives: We evaluated cross‐sectional associations between eating behaviours and cardiometabolic risk among 185 adolescents (age 12.4 ± 0.7 years; 53% female; body mass index (BMI)‐z 0.72 ± 1.37) from Cincinnati, Ohio (HOME Study; enrolled 2003–2006). Methods: Caregivers assessed adolescents' eating behaviours with the Child Eating Behaviour Questionnaire. We computed adolescents' cardiometabolic risk scores based on HOMA‐IR, triglycerides to high‐density lipoprotein cholesterol ratio, adiponectin to leptin ratio, systolic blood pressure, and cross‐sectional area of fat inside the abdominal cavity. Using multivariable linear regression models, we estimated associations of eating behaviour subscales with cardiometabolic risk scores or individual risk components. Results: Emotional overeating (ß = 1.34, 95% CI: 0.67, 2.01), food responsiveness (ß = 0.99, 95% CI: 0.41, 1.57), and emotional undereating (ß = 0.64, 95% CI: 0.08, 1.21) were associated with higher cardiometabolic risk scores. Satiety responsiveness (ß = −0.79, 95% CI: −1.59, 0.00) was associated with lower cardiometabolic risk scores. Adjusting for adolescent BMI‐z at age 12 attenuated these associations, suggesting that adiposity may mediate these associations. Conclusion: Hedonistic eating behaviours were associated with higher cardiometabolic risk in these adolescents.